Since it is not indicated that "x\\in\\mathbb{R}^n" , so I will assume for simplicity that
"\\partial^\\beta\\left(x^\\alpha\\right)\\equiv d^\\beta\\left(x^\\alpha\\right)" Remarks: in the condition there is an expression "\\left(\\alpha,\\,\\beta\\right)" - this is a binomial coefficient.When solving the problem, I will write it in the traditional form
"\\left(\\alpha,\\,\\beta\\right)\\equiv\\dbinom{\\alpha}{\\beta}\\equiv\\frac{\\alpha!}{\\beta!\\cdot(\\alpha-\\beta)!}"
( More information: https://en.wikipedia.org/wiki/Binomial_coefficient )
Next, by definition
"d\\left(x^\\alpha\\right)=\\alpha\\cdot x^{\\alpha-1}\\quad\\textnormal{Power rule}\\\\[0.5cm]\nd^n\\left(f\\right)=d^{n-1}\\left(d\\left(f\\right)\\right)\\equiv d^{n-1}\\left(f'\\right)"
( More information: https://en.wikipedia.org/wiki/Differentiation_rules )
Then,
"d^\\beta\\left(x^\\alpha\\right)=d^{\\beta-1}\\left(d\\left(x^\\alpha\\right)\\right)=\nd^{\\beta-1}\\left(\\alpha\\cdot x^{\\alpha-1}\\right)=\\\\[0.3cm]\n=\\alpha\\cdot d^{\\beta-2}\\left( d\\left(x^{\\alpha-1}\\right)\\right)=\n\\alpha(\\alpha-1)\\cdot d^{\\beta-2}\\left(x^{\\alpha-2}\\right)=\\\\[0.3cm]\n=\\ldots=\\alpha(\\alpha-1)\\cdot\\ldots\\cdot(\\alpha-(\\beta-1))\\cdot x^{\\alpha-\\beta}=\\\\[0.3cm]\n=\\frac{\\alpha(\\alpha-1)\\cdot\\ldots\\cdot1}{(\\alpha-\\beta)\\cdot\\ldots(1)\\cdot\\beta!}\\cdot \\beta!\\cdot x^{\\alpha-\\beta}=\\frac{\\alpha!}{(\\alpha-\\beta)!\\cdot\\beta!}\\cdot\\beta!\\cdot x^{\\alpha-\\beta}"
Conclusion,
"\\boxed{d^\\beta\\left(x^\\alpha\\right)=\\frac{\\alpha!}{(\\alpha-\\beta)!\\cdot\\beta!}\\cdot\\beta!\\cdot x^{\\alpha-\\beta}\n\\equiv\\dbinom{\\alpha}{\\beta}\\cdot\\beta!\\cdot x^{\\alpha-\\beta}}"
Q.E.D.
Comments
Dear Rachel. Thank you for a clarification.
The "β≤a" at the end of the question should be situated under Σ.
Leave a comment